Aktivitas Antihiperglikemik Kombinasi Ekstrak Etanol Daun Yakon (Smallanthus sonchifolius) dan Metformin pada Mencit yang Diinduksi Aloksan - Lidia Kurniawati; Dwi Ningsih; Vivin Nopiyanti (Jurnal Farmasi Indonesia, 2014)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia and related with abnormality metabolism of carbohydrate, lipid, and protein cause a decrease of insulin secretion or insulin sensitivity decrease or both. Yakon leaves is traditional medicinal plants that one of benefits could treat diabetes mellitus. The experiment was purpose to find antihyperglycemic activity of combination of yakon leaves ethanolic extract and metformin in mice induced alloxan. Test animals were divided in 6 groups each group consist of 5 mice. Groups I was given CMC 0,5%, group II was given metformin (65 mg/kg BB), group III was given yakon leaves ethanolic extract (840 mg/kg BB), group IV was given combination of yakon leaves ethanolic extract (420 mg/kg BB) and metformin (32,5 mg/ kg BB), group V was given combination of yakon leaves ethanolic extract (630 mg/kg BB) and metformin (16,25 mg/ kg BB). The treatment were given during 14 days, with measurement of glucose levels at 7 days and 14 days, then it was statistically tested by one way analysis of variance at 95% confidence continued with Tukey test. The result showed that the combination of yakon leaves ethanolic extract (630 mg/kg BB) and metformin (16,25 mg/ kg BB) was better than metformin or yakon leaves ethanolic extract.